Evaluation of the corrosion resistance of electroless Ni-P coatings on magnesium - Ramírez,Laura Quiroz (2020)
ABSTRACT Magnesium and its alloys offer a wide range of applications due to their excellent properties, however, their high chemical reactivity depends on their possible application in environments that have high chloride contents, because the development of an efficient method of surface protection and Easy implementation on an industrial scale is necessary. In the present work, nickel-phosphorus (Ni-P) electrolytic coatings on magnesium substrates were obtained from a chromate-free method. Subsequently, these coatings were evaluated electrochemically by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) in NaCl 3.5% wt solution. The results indicate that the coatings obtained manage to produce greater thermodynamic stability to the magnesium surfaces and reduce approximately the corrosion rate by a factor of 1000. Therefore, the methodology for obtaining the Nickel-phosphorus coatings that we propose in this work is susceptible to industrial scale.